RBTT-01. RANDOMIZED PHASE 2 OPEN LABEL STUDY OF NIVOLUMAB PLUS STANDARD DOSE BEVACIZUMAB VERSUS NIVOLUMAB PLUS LOW DOSE BEVACIZUMAB IN RECURRENT GLIOBLASTOMA. (5th November 2018) - Ahluwalia, Manmeet; Peereboom, David; Schilero, Cathy; Forst, Deborah; Wong, Eric; Wen, Patrick; Reardon, David
Abstract: BACKGROUND: The outcome for glioblastoma (GBM) remains dismal with a median survival of 15 months. Vascular endothelial growth factor (VEGF) is a highly upregulated proangiogenic growth factor in GBM that contributes to tumor-associated immunosuppression by inhibition of dendritic cell maturation and antigen presentation, induction of apoptosis of CD8+ T cells and enhancing Treg activity. Hence, a combination of anti PD1 and anti VEGF is promising approach in recurrent GBM. Lower anti-VEGF therapy dosing can lead to enhanced immune infiltrate and improved survival following co-administration with an anti-tumor immunotherapeutic in preclinical studies. METHODS: This is a 90 patient randomized phase 2 open label study of nivolumab plus standard dose bevacizumab versus nivolumab plus low dose bevacizumab in recurrent GBM. Primary endpoint is to evaluate the efficacy of nivolumab when administered with standard and reduced dose bevacizumab as measured by overall survival (OS) at twelve months (OS-12). Secondary endpoint include safety, Progression free survival at 6 months, OS and overall response rate. Exploratory endpoints include circulating immunologic biomarkers, cytokines, archival tumor PD-L1 expression and inflammatory gene expression signature and perfusion and diffusion weighted imaging with response (RANO and iRANO). Eligibility Criteria include Age ≥ 18 years, first recurrence of GBM, normal organ function, KPS ≥ 70. Key exclusion criteria include active, known or suspected autoimmune disease, contraindications for bevacizumab therapy and decadron > 4 mg/ day or equivalent of steroids. STATISTICAL ANALYSIS: The one-sample log-rank test will be applied to outcomes observed for each arm individually to test the hypothesis that OS has been improved beyond the null 12-month survival rate of 45%. With N=45 patients per arm, a one-sided test provides power=0.80 to detect survival rate of 58% at 12-months following treatment at the 0.10 significance level. Results: The study (NCT03452579) is ongoing and enrolling GBM patients in first recurrence.